PENGARUH SOCIAL MEDIA MARKETING TIKTOK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SKINTIFIC DI BANJARMASIN - Anisa Fitri; Fitriyadi; Maryono; Irwansyah (Business Administration, FISIP ULM, 2024)
This research describes how the levels of Social Media Marketing and Brand Image influence Skintific Skincare Purchasing Decisions in Banjarmasin City. And this research aims to test the influence of Social Media Marketing and Brand Image on Purchasing Decisions The location of this research is Banjarmasin City. This research uses a quantitative approach, the sample taken was 100 respondents selected by accidental sampling with data collection using a questionnaire and data analysis using multiple linear regression analysis assisted by the IBM SPSS Statistics Version 25.0 program. The results of the research show that Social Media Marketing Tiktok has a partially significant effect on the decision to purchase Skintific Skincare in Banjarmasin City and Brand Image has a partially significant effect on the decision to purchase Skintific Skincare in Banjarmasin City. As well as Tiktok's Social Media Marketing and Brand Image simultaneously have a significant influence on Purchasing Decisions for Skintific Skincare in Banjarmasin City